Effect of Zanthoxylum bungeanum Maxim on the Lipid Oxidation and Fatty Acid Composition of Dry-Cured Fish During Processing - Zhang, J.; Xu, D.; Zhao, X.; Mo, H.; Fang, Zhongxiang (Wiley Online Library, 2017)
© 2016 Wiley Periodicals, Inc. The Chinese traditional dry-cured grass carp fish (Layú) was processed without (A) and with (B, 2%, W/W) Chinese prickly ash, Zanthoxylum Bungeanum Maxim, and the lipid oxidation and fatty acid composition of Layú were investigated. The addition of Chinese prickly ash showed no significant differences (P > 0.05) on the nutritional contents of Layú, but significantly inhibited the increase of ratio of polar oil, the content of free fatty acid, peroxide value and TBA (P < 0.05). It also inhibited the increase of saturated fatty acids in oil, and the decrease of the content of polyunsaturated fatty acid and polyunsaturated fatty acids during processing. Z. Bungeanum Maxim could effectively delay lipid oxidative decomposition. The contents of DHA and EPA were significantly higher (P < 0.05) in Layú B than Layú A. It can be concluded that Z. Bungeanum Maxim can display a protective effect against lipid oxidation during dry-cured fish processing. Practical Application: The addition of Chinese prickly ash can significantly inhibit the increase of ratio of polar oil, the content of free fatty acid, peroxide value and TBA (P < 0.05). Z. Bungeanum Maxim can effectively delay lipid oxidative decomposition and improve the quality of Layú.